Studi tentang Efektivitas Pembelajaran Bahasa Berbasis Game dalam Meningkatkan Keterampilan Berbicara Siswa - Rosita Endang Lestari; Tanzila Azizah Rahmi; Muhammad Khaerul Makhfudh (BADAN PENERBIT STIEPARI PRESS, 2022)
This study aims to evaluate the effectiveness of game-based language learning in improving students' speaking skills at the secondary school level. Game-based learning is considered an innovative approach that can enhance student motivation and engagement in language learning. The research employs an experimental design with an experimental group using game-based learning methods and a control group using conventional methods. Data were collected through speaking tests administered before and after the learning period and questionnaires assessing students' perceptions of the applied methods. The results indicate that the experimental group showed significant improvements in speaking skills compared to the control group. Students involved in game-based learning demonstrated progress in fluency, articulation, and confidence in speaking. The study suggests that integrating game-based learning methods more widely into the language curriculum could maximize students' speaking skills potential.